Why Human Beings Become Bad. The Early Stoic Doctrine of Double Perversion - Brouwer, René (ΠΗΓΗ/FONS, 2020)
In this article I offer a reconstruction of the early Stoics’ account of why human beings become bad, which they referred to as the doctrine of «double perversion», and place this doctrine in its Hellenistic context. I do so on the basis of the extant sources, going beyond the standard collections of evidence on the Stoics, and with particular emphasis on Calcidius’ account, which I suggest is somewhat longer than often assumed. The two causes the early Stoics identified are each first set out within Stoic thought itself and subsequently placed against the background of the debate about human conduct among the different schools of thought that emerged in the Hellenistic period. With regard to the first cause, persuasiveness of external matters, I maintain that the early Stoics in fact attacked the Epicureans, arguing that humans should not be misled by the pleasurable nature of some things. With regard to the second cause, verbal influence by others, the early Stoics actually followed Socrates and the Cynics in emphasizing the importance of thinking against common opinion.
Keywords: perversion (Greek; διαστροφή; Latin; perversio); badness; early Stoa; Epicurus; Cynics; Socrates; Calcidius